Recent Advancement in Therapeutic and Managemental Approaches of Mastitis in Dairy Animals - Saksham Mandawat; Rashmi Singh; Anita Sewag; Y.P. Singh; D.S. Meena; N.K. Jeph (Annals of Arid Zone, 2024)
Mastitis, an inflammation of the udder in dairy animals, continues to pose a significant challenge, affecting both animal welfare and the economic sustainability of the dairy industry. It leads to decreased production efficiency and increased culling rates, resulting in considerable financial losses. Bovine mastitis, primarily caused by bacterial pathogens, necessitates early detection for effective management. Although various diagnostic techniques are available, conventional therapies like antibiotics face limitations, particularly with the growing issue of antibiotic resistance. This highlights the urgent need for early and efficient pathogen identification in farm settings to enable targeted interventions. Efforts to address these challenges have led to the development of alternative methods such as stem cell therapy, natural secretory compounds, and nutritional strategies. However, the efficacy of these approaches in managing mastitis remains inadequately studied. Future research must prioritize the evaluation of these novel therapeutic options and focus on developing sustainable solutions to replace conventional antibiotic treatments, ensuring effective mastitis management while combating antibiotic resistance.